The delimitation of the continental shelf between Denmark, Germany and the Netherlands : arguing law, practicing politics? / A.G. Oude Elferink. - Oude Elferink, Alex G., 1962- (Cambridge University Press, 2013)
Alex G. Oude Elferink's detailed analysis of the negotiations between Denmark, Germany and The Netherlands concerning the delimitation of their continental shelf in the North Sea makes use of the full range of government archives in these three States. He looks at the role of international law in policy formulation and negotiations, and explores the legal context, political considerations and, in particular, oil interests which fed into these processes. He also explains why the parties decided to submit their disputes to the International Court of Justice and looks at the preparation of their pleadings and litigation strategy before the Court. The analysis shows how Denmark and The Netherlands were able to avoid the full impact of the implications of the Court's judgment by sidestepping legal arguments and insisting instead on political considerations.